Pengaruh Label Halal dan Brand Trust terhadap Keputusan Pembelian Masker Wajah Wardah Melalui Minat Beli - Inayatur Rosidah; Heri Prabowo; Bayu Kurniawan (Master Manajemen, 2025)
This study aims to analyze the influence of halal labels and brand trust on purchasing decisions for Wardah face masks through purchasing interest in Semarang City Students. The research method used is quantitative with data collection techniques through distributing questionnaires to 384 respondents who use Wardah face masks among Semarang City students. Data analysis was carried out using the Structural Equation Modeling (SEM) technique with the help of SmartPLS software. The results of this study indicate that halal labels do not have a significant effect on purchasing interest and purchasing decisions, brand trust has a significant effect on purchasing interest and purchasing decisions, in addition, purchasing interest is proven to be significant as an intervening variable for brand trust on purchasing decisions, and purchasing interest does not have a significant effect as an intervening variable for halal labels on purchasing decisions. These findings indicate that trust in a trusted product can increase purchasing interest and ultimately drive purchasing decisions. This study provides implications for companies to build brand trust in order to increase purchasing interest and consumer purchasing decisions, especially among students. In addition, the results of this study are expected to be a reference for further research that discusses consumer behavior in the halal cosmetics industry.